The E-MOSAICS project: tracing galaxy formation and assembly with the age-metallicity distribution of globular clusters - Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present 25 cosmological zoom-in simulations of Milky-Way-mass galaxies in the ‘MOdelling Star cluster population Assembly In Cosmological Simulati